LncRNAs in Immune and Stromal Cells Remodel Phenotype of Cancer Cell and Tumor Microenvironment - Li W; Zhang H; You Z; Guo B (Dove Medical Press, 2024)
Wenbin Li,1,2,* Haohan Zhang,3,* Zuo You,4 Baozhu Guo5 1Department of Clinical Oncology, Qianjiang Hospital Affiliated to Renmin Hospital of Wuhan University, Qianjiang, Hubei, People's Republic of China; 2Department of Clinical Oncology, Qianjiang Central Hospital of Hubei Province, Qianjiang, Hubei, People's Republic of China; 3Cancer Center, Renmin Hospital of Wuhan University, Wuhan, Hubei, People's Republic of China; 4Department of Traditional Chinese Medicine, Xianfeng County People's Hospital, Enshi, Hubei, People's Republic of China; 5Department of Pain, Renmin Hospital of Wuhan University, Wuhan, Hubei, People's Republic of China*These authors contributed equally to this workCorrespondence: Zuo You, Department of Traditional Chinese Medicine, Xianfeng County People's Hospital, Enshi, 445600, People's Republic of China, Email hbzyyouzuo@126.com Baozhu Guo, Department of Pain, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People's Republic of China, Email 18071120246@163.comAbstract: Emerging studies suggest that long non-coding RNAs (lncRNAs) participate in the mutual regulation of cells in tumor microenvironment, thereby affecting the anti-tumor immune activity of immune cells. Additionally, the intracellular pathways mediated by lncRNAs can affect the expression of immune checkpoints or change the cell functions, including cytokines secretion, of immune and stromal cells in tumor microenvironment, which further influences cancer patients' prognosis and treatment response. With the in-depth research, lncRNAs have shown great potency as a new immunotherapy target and predict immunotherapy response. The research on lncRNAs provides us with a new insight into developing new immunotherapy drugs and predicting the outcome of immunotherapy. With development of RNA sequencing technology, amounts of lncRNAs were found to be dysregulated in immune and stromal cells rather than tumor cells. These lncRNAs function through ceRNA network or regulating transcript factor activity, thus leading abnormal differentiation and activation of immune and stromal cells. Here, we review the function of lncRNAs in the immune microenvironment and focus on the alteration of lncRNAs in immune and stromal cells, and discuss how these alterations affect tumor growth, metastasis and treatment response.Keywords: lncRNA, immune and stromal cells, tumor microenvironment, differentiation, cytokine secretion